Determination of soft skills expected for professionals in the urban food system industry - Artavia-Rojas, Kenny Joel (Kansas State University, 2019)
The importance of soft skills in professional and life success is not a new concept but there is a growing awareness of these non-cognitive skills as part of the higher education experience, including in agriculture. In 2011 researchers identified seven soft skills needed for successful employment in agriculture, natural resources, and related careers and suggested they should be considered in curriculum revitalization. Currently, many universities successfully teach agriculture students technical skills and theoretical knowledge. However, to be successful, there is a clear and urgent need for agricultural professionals to develop soft skills. The goal of the Urban Food Systems graduate program at Kansas State University is to prepare students for positions such as director/program managers in not-for-profit organizations, city governments or extension programs in urban districts facilitating community gardens, urban farming, farmers markets, or farm-to-school programs. Thus, incorporating soft-skill development within this graduate program is critical. The objective of this study was to determine what soft skills are more important for professionals in the urban food systems industry (public, private, and nonprofit). A national survey was distributed to a variety of national list serves (e.g. Comfood, North America Food System Network). Seven soft skills were examined: experiences, team skills, communication skills, leadership skills, decision making/problem-solving skills, self-management skills, and professionalism skills; and each soft skill was described through seven descriptive characteristics. For example, effective written communication and communicate pleasantly and professionally are two of the seven descriptive characteristics listed within communication skills. Respondents were asked to rank these descriptive characteristics from most important to least important. Respondents were also asked to rank the seven major soft skill categories from most important to least important. Nonparametric analysis (Friedman Test) and Principal Component Analysis (PCA) were used to determine differences among and within the seven groups using the statistical software XLSTAT (P < 0.05, n=73). Most of the respondents were from not-for-profit organizations (49%) or extension (18%) and were involved in the hiring process (67%). Overall, communication skills and team skills were ranked most important and professionalism skills was ranked least important. However, there were differences between those in extension and not-for-profits and those that are involved in hiring and those that are not. Additionally, for most of the soft skills, there were also ranking differences across the seven experiences overall, as well as by where the respondents worked and if they were involved in the hiring process. Results also showed a strong correlation between extension and communication skills, while non-profit organizations presented a correlation with experiences and self-management skills. Although teamwork skills and communication skills were considered the most important soft skills, graduate students may need to obtain all of them, focusing on the ones that are priorities depending on their interest and their desire working area whether in extension, a non-profit or another type of business. Although these results cannot be extrapolated to other fields since the circumstances are specifically related to the urban food system field, they serve as starting point for further research in this area.
Keywords: Urban Food Systems; Soft Skills